An introduction to narrative generators how computers create works of fiction - Pérez y Pérez, Rafael 1964- (Oxford University Press, 2023)
"This book describes how computer programs can generate narratives and how studies of computational narrative can illuminate how humans tell stories. Combining an introduction to relevant concepts related to automatic storytelling with accessible descriptions of well-known computer programs that illustrate how such concepts are employed, the book is aimed at an interdisciplinary audience and assumes little or no background in computer science. The book introduces the most relevant techniques employed over the last 60 years for the development of computer models for narrative generation, including narrative templates, problem-solving, planning, author engagement and reflection, and statistical methods such as deep neural networks, ending with an examination of the societal implications of the development of automatic narrative generator systems."--
Keywords: Kreatives Schreiben; Literatur; Künstliche Intelligenz; Fiction / Authorship / Computer programs; Fiction / Technique / Data processing; Creative writing / Data processing; Artificial intelligence; Discourse analysis, Narrative; Roman / Art d'écrire / Logiciels; Création littéraire / Informatique; Intelligence artificielle; Discours narratif; artificial intelligence